Everything bad is good for you : how popular culture is making us smarter - Johnson, Steven, 1968- (New York [etc.] Penguin books, 2006)
The 10 billion video gaming industry is now the second-largest segment of the entertainment industry in the United States, outstripping film and far surpassing books. Reality television shows featuring silicone-stuffed CEO wannabes and bug-eating adrenaline junkies dominate the ratings. But prominent social and cultural critic Steven Johnson argues that our popular culture has never been smarter. Drawing from fields as diverse as neuroscience, economics, and literary theory, the author argues that the junk culture we're so eager to dismiss is in fact making us more intelligent. A video game will never be a book nor should it aspire to be-and, in fact, video games, from Tetris to the Sims to Grand Theft Auto, have been shown to raise IQ scores and develop cognitive abilities that can't be learned from books. Likewise, successful television, when examined closely and taken seriously, reveals surprising narrative sophistication and intellectual demands. This book is a hopeful and spirited account of contemporary culture. The author demonstrates that our culture is not declining but changing-in exciting and stimulating ways we'd do well to understand. The glow of the video game or television screen will never be regarded the same way again.
Keywords: Cultura de masas; Inteligencia; Psicología social; Medios de comunicación social